Natural discoidal lipoproteins with tiny modification for tumor extracellular dissociation in antitumor chemoimmunotherapy. (August 2021) - Zhang, Huaqing; Cheng, Hao; Han, Yue; Jin, Yi; Wang, Gang; Sun, Chenhua; Jiang, Wenxin; Han, Guochen; Sun, Bo; Jiang, Zijun; Yuan, Zhou; Zhou, Jianping; et al.
Abstract: Appealing cancer immunotherapy requires synchronous presentation of tumor antigens and immunoadjuvant. Herein, a "one-step" modification strategy is proposed to tinily remould endogenous discoidal high density lipoprotein (dHDL) for tumor-homing and site-specific chemoimmunotherapy. For molecular targeting therapy, lipophilic immunoadjuvant CpG oligodeoxynucleotides is conjugated to facilitate HDL-surface anchoring; and GC nucleotides provide enough reservoir for completion of doxorubicin (Dox) "sandwich". After administration, the tiny size ( 30 nm) of disc nanodrug can maneuver deeply into tumors for receptor binding and in situ structural collapse. The intracellular concentrated CpG-Dox induce potent immunogenic cell death from burst Dox liberation at acidic pH. In turn, the released antigens and CpG motifs are simultaneously recognized by dendritic cells for antigen presentation and antitumor T cell responses. Combination chemoimmunotherapy with discoidal nanodrugs performed highest tumor weight inhibitory of 93.2% and extend the median survival time at a safe level. Collectively, this study suggests that the minimalist revolution of natural dHDL particulates may provide a biomimicry nanoplatform for site-specific amplified chemoimmunotherapy. Graphical abstract: A "one-step" modification strategy was proposed to functionalize natural discoidal HDL into a multifunctional nanoplatform for codelivery of Dox and CpG, which works for tumor cell destruction with site-specific antigen release and activates the immune cells, respectively, acting as in situ tumor vaccine. Image 1